2019
DOI: 10.21608/adjg.2019.7808.1103
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antimicrobial Efficacy of Chitosan as Root Canal Irrigant on Enterococcus faecalis

Abstract: Purpose:To evaluate the antimicrobial effect of chitosan as root canal irrigant on Enterococcus faecalis in comparison to 3%NaOCL in experimentally infected primary anterior root canals. Materials and methods: Access cavity and mechanical preparation of root canals of 30 extracted primary anterior teeth which were then sterilized at autoclave at 121 0 for 15 minutes. These teeth inoculated with Enterococcus faecalis with reference strain ATCC 19433.Then grouped into three groups which were irrigated with 3%NaO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In a study it was revealed that the positively charged chitosan interacted with the negative charge of bacterial cell elevating permeability of bacterial cell, resulting in leakage of intercellular components and cell death. In addition, chitosan can attach to DNA and inhibit mRNA synthesis through nucleus of microorganism and interfere with mRNA and synthesis of protein, correlated with capability of wound healing which may explain the results of our study that has shown no statistical significance between all groups (20) . In a recent study chitosan was capable of decreasing bacterial and fungal growth; where the presence of normal PDL in this study radiographs could be attributed to explaining as well the absence of any loss of lamina dura and neither internal or external resorption occurring too (21) .…”
Section: Discussionmentioning
confidence: 59%
“…In a study it was revealed that the positively charged chitosan interacted with the negative charge of bacterial cell elevating permeability of bacterial cell, resulting in leakage of intercellular components and cell death. In addition, chitosan can attach to DNA and inhibit mRNA synthesis through nucleus of microorganism and interfere with mRNA and synthesis of protein, correlated with capability of wound healing which may explain the results of our study that has shown no statistical significance between all groups (20) . In a recent study chitosan was capable of decreasing bacterial and fungal growth; where the presence of normal PDL in this study radiographs could be attributed to explaining as well the absence of any loss of lamina dura and neither internal or external resorption occurring too (21) .…”
Section: Discussionmentioning
confidence: 59%
“…This is because chitosan exhibits antimicrobial activity due to the electrostatic interactions between amino group (NH 3+ ) which binds to the bacterial cell surface and hence altering the cell permeability and results in the leakage of intracellular components and finally cell death (10) . Moreover, chitosan can attach to bacterial DNA by passing to the microorganisms' nuclei and interfering with proteins synthesis (27) . However, the results of the use of 6% citric acid as an irritant solution in this study resulted in a decrease in E. faecalis count.…”
Section: Discussionmentioning
confidence: 99%